Prestige, Recognition, and Social Rivalry in California in Kristin Hannah’s The Women - Auriellia, Rivandha Putri; Rikza, Nur Qolbiyatur; Kusumajanti, Wahju (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the representation of prestige, recognition, and social rivalry in Californian society in Kristin Hannah’s The Women. This research analyzes how family prestige influences Frankie’s decision to participate in the war, how recognition is constructed for returning veterans in Californian society, and how social rivalry produces acceptance and exclusion that affect the protagonist's identity formation before and after the Vietnam War. The study applies René Girard's mimetic theory to examine how the desire for prestige and recognition emerges through social imitation and develops into rivalry in postwar society. The findings show that Californian society functions as a social arena in which prestige motivates participation in war, recognition is unequally distributed between male soldiers and female nurses, and rivalry over legitimacy shapes the protagonist’s postwar identity transformation. The study concludes that prestige, recognition, and rivalry serve as central social mechanisms that influence both personal motivation and social acceptance in the novel.